CD47 expression in non-small cell lung cancer and its relationship with tumor-associated macrophage infiltration. - Hefeng Zhang; Shihu Liu; Jinzi Zhang; Yongjie Wang (PLoS ONE)
Background Non-small cell lung cancer (NSCLC) has a high incidence, with most patients diagnosed beyond the optimal surgical window. Improving survival rates is critical to reducing lung cancer mortality, and identifying immune checkpoints is vital for prognosis stratification. Objective To investigate the expression of CD47 in NSCLC and its relationship with tumor-associated macrophage infiltration. Methods A retrospective analysis was conducted on 50 NSCLC patients treated between January 2014 and June 2018. Immunohistochemistry and confocal microscopy assessed CD47 expression in tumor and adjacent tissues, while immunofluorescence evaluated CD47 on tumor-infiltrating T lymphocytes. Kaplan-Meier survival analysis and Cox regression identified prognostic factors, and PLA technology examined CD47's interaction with VEGFR and CD36. Results CD47 positivity in tumor tissues (52%) was significantly higher than in adjacent tissues (20%) (P<0.001), with expression localized to the cell membrane. CD47 expression correlated with lymph node metastasis, clinical stage, and differentiation (P<0.05) and was identified as an independent risk factor for poor prognosis. TAM infiltration was greater in CD47-positive patients and correlated with shorter survival (P<0.05). PLA showed stronger CD47+VEGFR interactions than CD47+CD36. Conclusion CD47 positivity correlates with poor prognosis and increased TAM infiltration, highlighting its potential as a prognostic biomarker and therapeutic target in NSCLC.